Longing and belonging through migration: Otherness and empathy in theatre and philosophy. (1st November 2019) - Corrêa, Graça P.
AbstractThis article examines how theatre and philosophy may critically contribute to discussing empathy towards otherness in the context of the ongoing massive surge of migration across the globe. Drawing on concepts from philosophical works by Baruch Spinoza, Henri Bergson and Jacques Derrida, it investigates how different dramaturgical techniques and aesthetics ‐ namely in Euripedes' Children of Heracles (c.430 BCE), Roland Schimmelpfennig's The Golden Dragon (2009) and Nikos Kazantzakis and Graça P. Corrêa's Christ Recrucified (1954/2018) ‐ address ethical-affective percepts such as empathy and hospitality in a theatre dealing with migration experiences.